Role of Vitamin E and Vitamin C in Oxidative Stress of Female Reproductive System (Global Journal of Medical Research, 2022)
This study is done to measure the role of vitamin C and vitamin E as an antioxidant on the oxidative stress of female reproductive system This study explained that reactive oxygen species and oxidative stress remain in balance to prevent the human body from adverse effects of oxidative stress This study explained that reactive oxygen species affect the multiple physiological functions of female reproductive system such as maturation of oocyte from fertilization development of embryo and pregnancy This is a case study report based on the previous studies to measure and assess the findings of other scholars about the effect of vitamin E and vitamin C on the oxidative stress on female reproductive system Thus the results of this study concluded that Vitamin E and vitamin C act as a defense partners against oxidative stress in female reproductive system